Dataset associated with "The C2A domain of synaptotagmin is an essential component of the calcium sensor for synaptic transmission" - Bowers, Matthew; Reist, Noreen (Colorado State University. Libraries, 2020)
The synaptic vesicle protein, synaptotagmin, is the principle Ca2+ sensor for synaptic transmission. Ca2+ influx into active nerve terminals is translated into neurotransmitter release by Ca2+ binding to synaptotagmin's tandem C2 domains, triggering the fast, synchronous fusion of multiple synaptic vesicles. Two hydrophobic residues, shown to mediate Ca2+-dependent membrane insertion of these C2 domains, are required for this process. Previous research suggested that one of its tandem C2 domains (C2B) is critical for fusion, while the other domain (C2A) plays only a facilitatory role. However, the function of the two hydrophobic residues in C2A have not been adequately tested in vivo. Here we show that these two hydrophobic residues are absolutely required for synaptotagmin to trigger vesicle fusion. Using in vivo electrophysiological recording at the Drosophila larval neuromuscular junction, we found that mutation of these two key C2A hydrophoic residues almost completely abolished neurotransmitter release. Significantly, mutation of both hydrophobic residues resulted in more severe deficits than those seen in synaptotagmin null mutants. Thus, we report the most severe phenotype of a C2A mutation to date, demonstrating that the C2A domain is absolutely essential for synaptotagmin's function as the electrostatic switch.
The dataset includes all electrophysiological, western, and immunohistochemical data and its analysis. Also included are unedited representative blots and traces. All data was complete as of 2019.01.09.
College of Veterinary Medicine and Biomedical Sciences
Department of Biomedical Sciences
Keywords: synapse; neuroscience; vesicle fusion; neurotransmitter release; synaptotagmin